2001
DOI: 10.1046/j.1365-2346.2001.00870.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibreoptic views through the laryngeal mask and the intubating laryngeal mask

Abstract: The view of the laryngeal inlet is better through the laryngeal mask airway than through a tracheal tube inserted to 18 cm in the intubating laryngeal mask.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…McNeillis et al compared the laryngeal view from a bronchoscope passed through a cLMA, with the view from a tracheal tube inserted to 18 cm inside an ILMA. They found that the vocal cords were visible in 92% of cases in the former technique, vs 52% in the latter [16]. Like us, they speculate that the reason for the inferior endoscopic view via the ILMA was the increased depth of insertion of the bronchoscope, necessary to lift the epiglottis elevator bar.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…McNeillis et al compared the laryngeal view from a bronchoscope passed through a cLMA, with the view from a tracheal tube inserted to 18 cm inside an ILMA. They found that the vocal cords were visible in 92% of cases in the former technique, vs 52% in the latter [16]. Like us, they speculate that the reason for the inferior endoscopic view via the ILMA was the increased depth of insertion of the bronchoscope, necessary to lift the epiglottis elevator bar.…”
Section: Discussionmentioning
confidence: 74%
“…Other authors have also reported inferior fibreoptic positioning of the ILMA compared with the cLMA [4,15,16]. Keller and Brimacombe [15] suggest that the fixed length of the airway tube of the ILMA may be responsible.…”
Section: Discussionmentioning
confidence: 99%
“…The stopwatch was then stopped (Time 1) and the investigator checked the position of the airway using a fibreoptic endoscope. The view was graded by investigators using a validated fibreoptic scoring system [7]: • full view of vocal cords: grade 1;…”
Section: Methodsmentioning
confidence: 99%
“…The bevel may be deflecting the FOS and making passage of the FOS in the trachea more difficult. McNeillis et al found that the view of the laryngeal inlet through the cLMA was better than through the ILMA and an 8-mm Euromedical tracheal tube, inserted to 18 cm to lift the epiglottic bar [7]. Keller and Brimacombe reported that the fibreoptic positioning of the ILMA was inferior to that of the cLMA [16].…”
Section: ó 2007 the Authorsmentioning
confidence: 99%
“…However, there was a suggestion of more malalignment in the PLA group (P=0.06). The degree of alignment may help to predict the ability of an airway device to assist in endotracheal intubation 24 . The success of the LMA in endotracheal intubation has been well documented 25,26 .…”
Section: Laryngeal Alignmentmentioning
confidence: 99%